Design and Validation of a Medicinal Plant Diversity Learning Module Based on Research in Las-Lasan Village Klaten for High School Students - Asy-Syifaiyah, Asma’; Nugroho, Anwari Adi (Journal of Biology Learning, 2025)
This study examines the diversity of medicinal plants in Las-Lasan Village, Klaten, and develops a research-based learning module for high school students. This research is part of a research and development project encompassing the following stages: preliminary study, planning, initial product development, revision of the initial product, limited field testing, and revision of the second product. The learning module design is based on existing learning modules used in high schools and integrated with the research findings on medicinal plant diversity. The learning module was validated by learning module experts and experts in plant diversity. Data analysis of expert validation results was conducted using quantitative descriptive analysis. The study concludes that the medicinal plant diversity learning module based on research in Las-Lasan Village, Klaten is highly feasible for use in high school biology learning. By integrating empirical data, the module enhances students’ understanding of ecology and biodiversity, promotes independent learning, and supports contextual, critical, and applicable education.